Bone mineral status of young cyclists - Dlugolecka, B. (Theory and Practice of Physical Culture, 2020)
The aim of this work was to assess bone mineral content (BMC) and bone mineral density (BMD) in men practicing road cycling at peak bone mass in comparison with men at the same age not practicing sport. Road cyclists, representatives of youth cycling clubs (n=30) aged 21-22 and men of similar age who do not practice sports (n=45) took part in the research. BMC (g) and BMD (g/cm2) in the lumbar spine (L2-L4) were determined with the use of the DEXA method.The analysis of the results showed that the mean values of the determined bone parameters did not differentiate the studied groups. However, tendencies to higher values in the control group were observed. Excessive phosphorus intake was observed in both groups. On the basis of the results obtained it can be concluded that the examined cyclists do not constitute a group of increased risk of developing osteopenia in comparison with men who do not train.